Understanding Consumers’ Intentions to Purchase Technological Innovations in the Context of Sport - Selvaratnam, Vinurshan (University of Waterloo, 2024)
Researchers have studied innovation adoption in various sport contexts, including digital ticketing, sport team mobile apps, fantasy sports league websites, and smart-connected sports products, to name a few. However, researchers have yet to examine consumers’ acceptance of the Apple Vision Pro. This is primarily because the Apple Vision Pro is a new technology that was just introduced to the public in February 2024. Understanding consumers’ acceptance of the Apple Vision Pro is warranted since anecdotal evidence suggests it can positively impact the fan experience. In this dissertation, I conducted three studies to better understand sport consumers’ acceptance of the Apple Vision Pro by applying and extending the Technology Acceptance Model (TAM), a theory widely used to study innovation adoption. For all three studies, online surveys designed through Qualtrics were used to collect data (n=272) from Prolific Academic, an online crowdsourcing platform used for behavioral research. In study 1, I included team identification into the TAM to explain why and how sport consumers accept the Vision Pro. To analyze data, structural equation modeling was used and the findings showed that private evaluation and cognitive awareness, two dimensions of team identification, had an indirect positive effect on purchase intention through perceived usefulness, perceived ease of use, and attitude. As such, I recommend that marketers and technology developers implement strategies highlighting the usefulness and ease of use of technologies such as the Vision Pro. I also recommend targeted marketing strategies that appeal to the emotional and cognitive aspects of team identification, leading to purchase intentions among sports fans. In study 2, I included constructs from innovation diffusion theory into the TAM to better understand consumers’ acceptance of the Apple Vision Pro. Structural equation modeling was used to analyze data. The findings showed that compatibility, trialability, and observability positively and indirectly influenced purchase intention through perceived usefulness, perceived ease of use, and attitude. As such, I argue that marketing strategies for the Vision Pro should not only focus on demonstrating its unique features and benefits but also emphasize its compatibility with users' lifestyles, offer new opportunities to try the technology for sports fans, and showcase the benefits accrued by existing users. Finally, in study 3, I included perceived monetary value and financial risk into the TAM to understand sports consumers' acceptance of the Vision Pro. Structural equation modeling was used to analyze data. The findings showed that perceived financial risk indirectly influenced purchase intention through attitude. This suggests that while perceived financial risk directly influences consumers' attitudes, these attitudes then significantly shape consumers’ purchase intention of the Apple Vision Pro. As such, I argue that marketers should focus on enhancing the positive aspects of the Vision Pro to promote favorable attitudes among sport consumers. For instance, showcasing the unique features of the Vision Pro and emphasizing its benefits in enhancing the fan experience can enhance positive attitudes and offset the negative impact of perceived financial risks. Theoretically, this dissertation extends the TAM by showing the value of integrating other theories and concepts relevant to the study of innovation adoption. This dissertation also advances understandings of technology acceptance in the context of sport by revealing one of the unique features of sport, namely team identification, and its role in adoption. Therefore, exploring the complex interplay of various factors influencing the adoption of the Apple Vision Pro not only validates existing theories but also provides new insights and perspectives, thus paving the way for further research.
Keywords: technological innovation; technology acceptance model; sports fans